Faktor Risiko Kurang Energi Kronis (KEK) Pada Ibu Hamil Di Kecamatan Harjamukti Kota Cirebon - Yusriyani, Atikah; Budiono, Irwan (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Harjamukti subdistrict is one of the subdistricts in Cirebon that has a high prevalence of CED pregnant women, which is 38.7%. This study aims to determine the factors associated with the incidence of CED in pregnant women in the Harjamukti subdistrict. The study used a case-control design with purposive sampling techniques. The number of respondents was 39 cases and 39 controls. Data analysis using chi-square test and logistic regression test. Parity, pregnancy spacing, average level of energy intake, education level, family income level, and culture of food abstinence are factors associated with the incidence of CED in pregnant women.